Reduced EAAT1 and mGluR5 expression in the cerebellum of FMR1 premutation carriers with FXTAS - Pretto, Dalyir I. (2013)
A premutation (PM) expansion (55–200 CGG) in the fragile X mental retardation gene 1 (FMR1) causes elevated mRNA and reduced FMR1 protein (FMRP). Young PM carriers can develop characteristic physical features and mild cognitive disabilities. In addition, individuals with PM, particularly male carriers, are at high risk to develop Fragile X-associated tremor/ataxia syndrome (FXTAS) with aging. Human post-mortem FXTAS brains show extensive white matter disease in the cerebellum and the presence of intranuclear inclusions throughout the brain, although their etiological significance is unknown. In the current work, expression levels of the metabotropic glutamate (Glu) receptor mGluR5 and the Glu transporter EAAT1, examined by RT-PCR and WB analyses, were found to be reduced in the post-mortem cerebellum of PM carriers with FXTAS compared to age matched controls, with higher CGG repeat number having greater reductions in both proteins. These data suggests a dysregulation of Glu signaling in PM carriers, which would likely contribute to the development and severity of FXTAS.